WOVOdat – the global volcano unrest database aimed at improving eruption forecasts. Issue 6 (4th November 2019) - Costa, Fidel; Widiwijayanti, Christina; Nang, Thin Zar Win; Fajiculay, Erickson; Espinosa-Ortega, Tania; Newhall, Christopher
Abstract : Purpose: The purpose of this paper is to highlight the importance of a comprehensive global database on volcanic unrest (WOVOdat) as a resource to improve eruption forecasts, hazard evaluation and mitigation actions. Design/methodology/approach: WOVOdat is a centralized database that hosts multi-parameter monitoring data sets from unrest and eruption episodes of volcanoes worldwide. Its online interface (https://wovodat.org/ ) allows interactive data analysis and comparison between volcanoes and eruption styles, which is needed during volcanic crises, as well as to perform basic research on pre-eruption processes, teaching and outreach. Findings: WOVOdat aims to standardize and organize the myriad of monitoring data types at the global scale. Users can compare changes during a crisis to past unrest episodes, and estimate probabilities of outcomes using evidence-based statistics. WOVOdat will be to volcanology as an epidemiological database is to medicine. Research limitations/implications: The success of eruption forecast relies on data completeness, and thus requires the willingness of observatories, governments and researchers to share data across the volcano community. Practical implications: WOVOdat is a unique resource that can be studied to understand the causes of volcanic unrest and to improve eruption forecasting. Originality/value: WOVOdat is the only compilation of standardized and multi-parameter volcano unrest data from around the world, and it is freely and easily accessible through an online interface.